2019
DOI: 10.1007/s00170-019-03834-8
|View full text |Cite
|
Sign up to set email alerts
|

The fast constant engagement offsetting method for generating milling tool paths

Abstract: It is a well-established fact that when equidistant tool paths are used for 2.5D milling operations tool load varies based on the functions of path curvature. This phenomenon makes the optimal selection of cutting parameters more difficult, and the local load peaks are also detrimental to machining stability and tool life. Numerous publications address possible solutions to eliminate the problems caused by varied cutting parameters. The best solution for this is to keep the cutter engagement at a constant valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…4A. The effort towards maintaining a constant chip-thickness through varying the input parameters is bene cial to extend the tool life [47].…”
Section: Discussion On Various Intelligent Grinding Systems Previous Intelligent Grinding Systemsmentioning
confidence: 99%
“…4A. The effort towards maintaining a constant chip-thickness through varying the input parameters is bene cial to extend the tool life [47].…”
Section: Discussion On Various Intelligent Grinding Systems Previous Intelligent Grinding Systemsmentioning
confidence: 99%
“…The cutting strategy was optimized assuring that during the change of the feed direction (i.e., workpiece corner) the tool remains in contact with the workpiece keeping a constant load (constant stepover offsetting). This was done using an approach similar to the one reported in Jacso et al [23]. Moreover, when it was requested to stop the cutting to analyze the tool (for a scheduled stop or for a supplementary check), it was smoothly disengaged from the piece with a circular trajectory.…”
Section: Methodsmentioning
confidence: 99%
“…This irregular tool loading is undesirable for a number of reasons. It has been shown in multiple studies that having a constant engagement of the tool with the workpiece, and therefore constant cutting force, can improve tool wear by minimizing cutting force spikes and improve machining accuracy by minimizing the variations of the tool's deflection during cutting [28,29]. This would be beneficial in decreasing chatter as well, since Chuangwen et al [30] found that increased tool wear and cutting depth led to increased amplitude of cutting vibrations that can lead to regenerative chatter [31].…”
Section: Introductionmentioning
confidence: 99%